Curaxin CBL0137 Exerts Anticancer Activity via Diverse Mechanisms - Jin, Ming-Zhu; Xia, Bai-Rong; Xu, Yu; Jin, Wei-Lin (Frontiers in Oncology, 2018)
Chemotherapy with or without radiation remains the first choice for most cancers. However, intolerant side effects and conventional drug resistance restrict actual clinical efficacy. Curaxin CBL0137 is designed to regulate p53 and nuclear factor-κB simultaneously and to prevent the resistance caused by a single target. Functionally, CBL0137 exhibits an antitumor activity in multiple cancers, including glioblastoma, renal cell carcinoma, melanoma, neuroblastoma, and small cell lung cancer. Mechanistically, CBL0137 is originally identified to act by facilitates chromatin transcription complex. Further investigations reveal that several pathways, such as NOTCH1 and heat shock factor 1, are involved in the process. CBL0137 has been reported to target cancer stem cells and enhance chemotherapy/monotherapy efficacy. The translational advance of CBL0137 into clinical practice is expected to provide a promising future for cancer treatment.